2022
DOI: 10.1002/jbio.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy and supervised learning as a potential tool to identify high‐dose‐rate‐brachytherapy induced biochemical profiles of prostate cancer

Abstract: High‐dose‐rate‐brachytherapy (HDR‐BT) is an increasingly attractive alternative to external beam radiation‐therapy for patients with intermediate risk prostate cancer. Despite this, no bio‐marker based method currently exists to monitor treatment response, and the changes which take place at the biochemical level in hypo‐fractionated HDR‐BT remain poorly understood. The aim of this pilot study is to assess the capability of Raman spectroscopy (RS) combined with principal component analysis (PCA) and random‐for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…An advantage of using RF for classification is the ability to evaluate the importance of the identified predictor variables for correct classification. 73,74 The ten most important PCs to correctly classify the data as irradiated and non-irradiated for 1, 4 and 24 hours post irradiation are shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 99%
“…An advantage of using RF for classification is the ability to evaluate the importance of the identified predictor variables for correct classification. 73,74 The ten most important PCs to correctly classify the data as irradiated and non-irradiated for 1, 4 and 24 hours post irradiation are shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, RS has demonstrated the potential to be incorporated into radiation therapy as a label-free technique to reveal the biochemical dynamics and assess the treatment response for various types of cancer. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] Nevertheless, conventional unsupervised dimension reduction techniques can provide limited resolution in distinguishing responses from different chemicals. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] In this manuscript, the GBR-NMF-RF-SHAP data analytical framework has demonstrated an outstanding capability to resolve signals such as radiation response and hypoxia indicators corresponding to constrained chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][59][60][61][62][63] Nevertheless, conventional unsupervised dimension reduction techniques can provide limited resolution in distinguishing responses from different chemicals. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] In this manuscript, the GBR-NMF-RF-SHAP data analytical framework has demonstrated an outstanding capability to resolve signals such as radiation response and hypoxia indicators corresponding to constrained chemicals. Moreover, GBR-NMF-RF-SHAP also exhibited efficiency in analyses across various types of cancer data (cell and tissue).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, the complex Raman scattering spectra of a cell can be effectively used as a “cell fingerprint” using machine learning in combination. Because of the high-content data obtained by Raman spectroscopy, it is compatible to other machine learning methods such as random-forest classification, support vector machine or k-means classification and being used in cancer diagnosis or evaluation of cancer treatment [ 33 , 34 , 35 ]. Use of Raman spectra in cancer discrimination is recently becoming popular in combination with machine-learning, including artificial intelligence [ 35 , 36 , 37 ], which is expected to further develop in the near future.…”
Section: Use Of Machine Learning On Raman Spectrum Analysismentioning
confidence: 99%